Friction and Wear Properties of MoCN, MoCN+MoS2 and MoCN+CFilms in Wide Temperature Range - BAO Bi-xia, QIAN Jian-guo, LI Shu-xin, PU Ji-bin, MAO Chun-long, MAO Jin-gen, CHEN Shan-jun (Cailiao Baohu)
In order to develop the coatings with low friction coefficient and low wear rate over a wide temperature range for aeroengine and gas turbine, MoCN, MoCN and MoS2 double layers and MoCN and C double layer films were deposited on 718 nickel-based superalloy and monocrystalline silicon substrate by unbalanced magnetron sputtering. The surface/cross section morphologies, composition and phase structures of the film were characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM) and X-ray diffractometry (XRD), and the hardness and elasticity of the films were investigated by MTS Nano Indenter G200 system. In addition, the friction tests of three films at different temperatures (25 ℃, 300 ℃, 500 ℃) were carried out by high temperature friction and wear tester (CSM) and the tribological mechanism of three films in wide temperature range was systematically studied. Results showed that the MoCN and C double-layer film exhibited the lowest friction coefficient of 0.09 at room temperature, the wear mechanism was mainly adhesive wear, while the MoCN single-layer film had the largest friction coefficient at room temperature, and the friction mechanism was mainly abrasive wear. When the friction temperature rised to 300 ℃, the top layers of MoS2 and C could improve the tribological properties of films by inhibiting the oxidation of the MoCN film. When the friction temperature rised to 500 ℃, the three films possessed severe oxidation behaviors, but the self-lubricating phase MoO3 formed at high temperature reduced the friction coefficient. Besides, the friction coefficient values of the three films were close.